Defaming and Defining 'Bloody Mary' in Nineteenth-Century England. Issue 1 (1st April 2014) - Richards, Judith M.
Abstract: Although the reputation of England's first queen regnant, Mary Tudor (died 1558) had remained substantially unchanged in the intervening centuries, there were always some defenders of that Catholic queen among the historians of Victorian England. It is worth noting, however, that such revisionism made little if any impact on the schoolroom history textbooks, where Mary's reputation remained much as John Foxe had defined it. Such anxiety as there was about attempts to restore something of Mary's reputation were made more problematic by the increasing number and increasingly visible presence of a comprehensive Catholic hierarchy in the nineteenth century, and by high-profile converts to the Catholic faith and papal authority. The pre-eminent historians of the later Victorian era consistently remained more favourable to the reign of Elizabeth, seen as the destroyer of an effective Catholic church in England.